2015
DOI: 10.1007/s10384-015-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for recurrence of macular edema after successful intravitreal bevacizumab therapy in branch retinal vein occlusion

Abstract: Early IVB treatment against BRVO may suppress ME recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…However, CME due to BRVO has a relatively high rate of recurrence. Only 30%–34% of IVB-effective eyes can achieve persistent resolution of CME, whereas most need additional treatments to optimize visual acuity [104106]. The duration from symptom onset to initial IVB could affect the CME recurrence rate but not the efficacy rate after a single IVB injection [104].…”
Section: Treatmentmentioning
confidence: 99%
“…However, CME due to BRVO has a relatively high rate of recurrence. Only 30%–34% of IVB-effective eyes can achieve persistent resolution of CME, whereas most need additional treatments to optimize visual acuity [104106]. The duration from symptom onset to initial IVB could affect the CME recurrence rate but not the efficacy rate after a single IVB injection [104].…”
Section: Treatmentmentioning
confidence: 99%
“…Several factors have been reported to be associated with the recurrences of the macular edema after the injection of an anti-VEGF agent, e.g., initial central retinal thickness (CRT), age, and several other factors 14–19 . However, it is still difficult to predict the number of recurrences even with knowledge of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Results of all pivotal trials on anti-VEGF treatment showed that gain in BCVA was limited initially as well as on the long-term, if treatment was deferred by 6-month sham treatment [ 4 , 5 , 8 , 11 , 14 ]. There is evidence that early anti-VEGF treatment may reduce the risk and frequency of recurrent macular edema [ 34 ].…”
Section: Discussionmentioning
confidence: 99%